Linguocognitive Bases of Language Teaching Methods of Forming Foreign Language Linguocultural Competence - Ушакова, Н. І. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article is devoted to the definition of the linguocognitive bases of language teaching methods of forming the linguocultural competence in the process of training a foreign language. The actuality of the research is defined by the fact that adequate communication is possible in the situation when the communicants speak in the necessary measure not only the language of communication but also the abilities to use the corresponding linguocultural thesaurus. The author characterizes linguoculturological and psycholinguoculturological approaches to defining the ways of foreign-language culture adequate interpretation which can form the basis for creating the language teaching methods of foreign language linguocultural competence formation. Linguoculture is a linguocognitive phenomenon, semantics of linguoculture – containing cultural meanings materialized in language signs. It has been considered the evolution of the main units of linguoculturological analysis (a linguoculturema, a linguoideologema, a concept, a frame structure, a linguocultural type, a meme). Such units are more complicated structural-semantic phenomena than the word as they possess the connotative content. For comparison of national conceptual systems it is possible to use the linguocognitive construct “culture code”. The comparison of language culture codes gives the chance to reveal the fragments of national mentalities which differ in similarity or their specifics of figurativeness. The code of culture models a world language picture and is fixed in lexical, phraseological, paroemialogical language fund. The author describes the possibilities of displaying theoretical achievements of linguoculturology in linguodidactics based on the example of learning the discipline “Culture-oriented linguistics” by foreign students-philologists, mastering of national-specific vocabulary groups (anthroponyms, toponyms, zoonyms), phraseological units, aphorisms, somatizms. Illustrations are given for the situation of mastering Russian as a foreign language. Creating the bank of linguocultural concepts and linguocultural types, structured according to the level of language proficiency, can become the direction of further methodical searches.